2017
DOI: 10.1016/j.jid.2016.10.045
|View full text |Cite
|
Sign up to set email alerts
|

TRPV4 ION Channel Is Associated with Scleroderma

Abstract: Critical evaluation of two primers commonly used for amplification of bacterial 16S rRNA genes. Appl Environ Microbiol 2008;74:2461e70. Kong HH. Details matter: designing skin microbiome studies. J Invest Dermatol 2016;136: 900e2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 15 publications
3
48
0
Order By: Relevance
“…Transforming growth factor β1 is known to induce EMT in keratinocytes . Recent evidence from our group suggests a link between TRPV4 activation and TGFβ1 signals that mediate fibroblast differentiation . Previous reports have documented that calcium signalling is involved in EMT in many cell types .…”
Section: Resultsmentioning
confidence: 86%
See 4 more Smart Citations
“…Transforming growth factor β1 is known to induce EMT in keratinocytes . Recent evidence from our group suggests a link between TRPV4 activation and TGFβ1 signals that mediate fibroblast differentiation . Previous reports have documented that calcium signalling is involved in EMT in many cell types .…”
Section: Resultsmentioning
confidence: 86%
“…We previously reported that TRPV4 KO mice are protected from pro‐fibrotic effects of bleomycin in lung and skin, and bleomycin has been shown to cause EMT in skin and pulmonary fibrosis model . To determine whether TRPV4 deficiency could also suppress EMT in an experimental model of skin fibrosis, we employed the bleomycin‐induced skin fibrosis model, and analysed expression of EMT markers between bleomycin or phosphate‐buffered saline (PBS) treated TRPV4 KO and WT mice.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations